In focus: where art meets science - Hennig, B; Dorling, D (SAGE Publications, 2016)
The United Kingdom, and especially England, has become geographically extremely unequal. This inequality is not only seen in growing economic disparities within the population, but also becomes increasing visible across all parts of public life, such as science and education, as well as the arts.